2020
DOI: 10.1186/s42466-020-00077-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of transient global amnesia during the Covid-19 crisis?

Abstract: Since the beginning oft he Covid-19 pandemic we have observed an increased incidence of transient global amnesia, possibly related to emotional stress as a trigger factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Further supporting this theory, a report from a neurological emergency department in a German academic hospital described an upsurge in patients with TGA thought to be due to increased stress levels from the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. An intake of 16 new patients with TGA was reported from February 1, 2020, to May 15, 2020, compared to an average number of just 9.7 that they received over the previous 10 years in total implying that social distancing, uncertainty of the future, and generalized fear may be contributing to increased stress levels leading to a greater incidence in TGA [ 6 ]. We can only speculate that stress levels may have played a role in the event that led to his confusion.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting this theory, a report from a neurological emergency department in a German academic hospital described an upsurge in patients with TGA thought to be due to increased stress levels from the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic. An intake of 16 new patients with TGA was reported from February 1, 2020, to May 15, 2020, compared to an average number of just 9.7 that they received over the previous 10 years in total implying that social distancing, uncertainty of the future, and generalized fear may be contributing to increased stress levels leading to a greater incidence in TGA [ 6 ]. We can only speculate that stress levels may have played a role in the event that led to his confusion.…”
Section: Discussionmentioning
confidence: 99%
“…Transient global amnesia (TGA) presents as an acute anterograde amnesia that generally resolves within 24 h. 1 Werner et al had noted increasing TGA since severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak in their hospital in Germany and reported 16 patients with TGA between February 1st and May 15th 2020 compared to their 10-year average of 9.7 2 In our series we noted 2 patients who presented with TGA secondary to acute hippocampal stroke in COVID-19 positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published retrospective cohort study on the neurological and psychiatric sequalae of COVID-19 in 236,379 patients [ 5 ] has shown that the incidence of ischemic stroke in about 10% of patients, majority with COVID-19 associated encephalopathy which is alarming and necessitates steps to prevent or manage in those already affected. Werner et al [ 6 ] have reported yet another neurological sequala, incidence of transient global amnesia during the COVID-19 hypothesizing the mechanism to be an encephalitic autoimmune pathology by the SARS CoV2 virus. Neurological manifestations of COVID-19 are thus postulated to be due to the binding of SARS-CoV-2 to ACE-2 activating intracellular pattern recognition receptors (PRRs) which sense the pathogen associated molecular patterns (PAMPs) setting off maladapted immune responses leading to inflammatory and immune activities disrupting the coagulation-embolism pathways in the CNS and PNS [ 7 ].…”
mentioning
confidence: 99%
“…The different types of cells in the CNS and PNS including the glial cells, neurons, endothelial and arterial smooth muscle cells are all affected leading to the neurological manifestations of COVID-19 [ 8 ]. However, the effects of SARS-CoV2 on human astrocytes, especially the microglia being the key-players in neural inflammation [ 6 ] makes us specifically focus on microglia in the context of conditions that involve neural- inflammation such as stroke, Parkinson's disease, Alzheimer's etc. For recovery, optimal functioning of the neuroglia is essential for synaptic organization, neurotrophic support, phagocytosis of apoptotic cells, debris removal, myelin turnover, control of neuronal excitability besides brain protection and repair.…”
mentioning
confidence: 99%